HUBUNGAN ANTARA SELF EFFICACY DENGAN LITERASI DIGITAL TERHAPAD MOTIVASI BELAJAR SISWA KELAS V SEKOLAH DASAR - Ramadhani, Afifah Dwi; Habibi, Mhmd (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This research aims to understand the self-efficacy and digital literacy of class V students at SDIT Al-Fityah Pekanbaru. The urgency of self-efficacy is that it can influence the way a person thinks, behaves, feels, and motivates himself. The population in this study was ninety fifth grade students, divided into three classes. The sampling technique in this research is purposive sampling with a sample size of 30 students in class V A. This research method is quantitative, with an analysis technique using the t test. The research results showed that student learning motivation and digital literacy were proven to be significantly correlated, based on the t-test results for the self-efficacy and digital literacy variables. The coefficient of determination test (R2) shows that self-efficacy and digital literacy together contribute 45.9% of the learning motivation of class V students at SDIT Al-Fityah Pekanbaru.